Head trauma and olfactory function - Jessica Howell (KeAi Communications Co., Ltd., 2018)
Olfactory impairment is a well-established sequela of head injury. The presence and degree of olfactory dysfunction is dependent on severity of head trauma, duration of posttraumatic amnesia, injuries obtained, and as more recently established, age. Deficits in smell can be conductive or neurosensory, contingent on location of injury. The former may be amenable to medical or surgical treatment, whereas the majority of patients with neurosensory deficits will not recover. Many patients will not seek treatment for such deficits until days, weeks, or even months after the traumatic event due to focus on more pressing injuries. Evaluation should start with a comprehensive history and physical exam. Determination of the site of injury can be aided by CT and MRI scanning. Verification of the presence of olfactory deficit, and assessment of its severity requires objective olfactory testing, which can be accomplished with a number of methods. The prognosis of posttraumatic olfactory dysfunction is unfortunate, with approximately only one third improving. Emphasis must be placed on identification of reversible causes, such as nasal bone fractures, septal deviation, or mucosal edema/hematoma. Olfactory loss is often discounted as an annoyance, rather than a major health concern by both patients and many healthcare providers. Patients with olfactory impairment have diminished quality of life, decreased satisfaction with life, and increased risk for personal injury. Paramount to the management of these patients is counseling with regard to adoption of compensatory strategies to avoid safety risks and maximize quality of life. Practicing otolaryngologists should have a thorough understanding of the mechanisms of traumatic olfactory dysfunction in order to effectively diagnose, manage, and counsel affected patients. Keywords: Anosmia, Head injury, Smell